2013
DOI: 10.1631/jzus.a1200146
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and structure improvement of double throttling in a high parameter pressure reducing valve

Abstract: In this paper, a new pressure reducing valve (PRV) with an orifice plate is proposed. The main objective is to explain the mechanisms of pressure reduction and energy conversion in the new PRV. A numerical simulation method was used to investigate the PRV internal flow field and to analyze the throttling effects of the orifice plate and the transform of thermal parameters as outlet pressure, outlet temperature, velocity, and superheat. A structure improvement method for the valve body and orifice plate is put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…The grid independence check of Valve B is listed in Table 1 [18]. Those grids were meshed with cells of different size.…”
Section: Computational Modelmentioning
confidence: 99%
“…The HPRV in Fig 1 [ 18 ] mainly consists of a forge-welded angle-type valve body, a conical plug and a perforated plate used for noise control. The perforated plate is a rounded flat plate with many through holes.…”
Section: Computational Modelmentioning
confidence: 99%
“…Flow through a contraction or expansion is a classical problem in fluid dynamics and its numerical modelling has a lot of applications such as nozzles (Xiong et al 2015;Allamaprabhu et al 2016), diffuser (Rosa and Pinho 2006;Mariani et al 2010) and throttling valves (Jin et al 2013). Other applications, with both combined geometries, are encountered in Venturi devices (Dong et al 2012;Maqableh et al 2012) and hemodynamics (Ikbal et al 2009;Ponalagusamy and Selvi 2013;Mandal et al 2011).…”
Section: Introductionmentioning
confidence: 99%